Pemanfaatan Limbah Fly Ash Pada Beton Mutu Tinggi Sebagai Bahan Tambah Untuk Campuran Beton - Muhammad Andi Rizki Ferdiansyah; Nurul Rochmah (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
Concrete with a compressive strength of more than 41.4 MPa is known as high strength concrete. High strength concrete is often used for precast concrete, especially for the construction of buildings, bridges, and also roads with wide spans. One of the materials used in this research is the addition of fly ash for concrete mixtures. Fly ash also has pozzolanic properties when mixed with other concrete mixtures. This research aims to analyze each proportion of fly ash used and also to determine the effect of using fly ash added materials, especially for compressive strength tests on high-quality concrete. In this study, fly ash was used with proportions of 0%, 5%, 10%, 12%, 15%, 20% using wcr 0.32 and also 0.4% superplasticizer level used. One of the tools used in this test is a cylindrical tube which has a size of 15 x 30 cm. Based on the research that has been done, the highest result for the test is 52.01 MPa for a percentage of 10% in 28 day concrete. It can be concluded that using fly ash material can increase the compressive strength of concrete by up to 10%, but the proportion above 10% decreases the compressive strength of concrete.